Case Report: Low pressure hyperbaric oxygen therapy as a potential alternative treatment for chronic inflammatory response syndrome: a case study with notable improvements in fatigue, cognition, and testing - Coletti Giesler, Kristen L. (Frontiers in Immunology, 2025)
Chronic Inflammatory Response Syndrome (CIRS), a complex condition triggered by environmental exposures such as mold toxins, remains challenging to treat effectively. This case study documents the incidental findings of hyperbaric oxygen therapy (HBOT) as a potential therapeutic intervention for CIRS. A 60-year-old female patient with persistent symptoms and abnormal laboratory markers underwent 40 shallow dive HBOT sessions over 10 weeks. Clinical evaluations included symptom scoring, visual contrast sensitivity (VCS) testing, and biomarker analysis, with pre-treatment tests conducted via Quest Diagnostics and post-treatment tests via LabCorp. Results demonstrated significant improvements: resolution of all 22 reported symptoms, normalization of VCS scores (from 68% to 93%), and notable reductions in inflammatory biomarkers, including TGF-β1 and MMP-9. This case illustrates HBOT’s ability to modulate systemic inflammation, improve neurocognitive outcomes, and enhance recovery in patients with complex environmental illnesses. While limited to a single-patient design, this study underscores the need for extensive quantitative research to validate HBOT’s efficacy in managing CIRS and similar conditions.